OPTIMALISASI PRODUKTIVITAS ALAT BERAT PADA PEKERJAAN PENGGALIAN SALURAN - Elena; Anna Rumintang Nauli; Elok Dewi Widowati (Racic : Rab Construction Research, 2026)
Drainage excavation is a crucial activity in road construction projects, relying heavily on the effectiveness of heavy equipment to achieve time and cost efficiency. This study aims to compare the theoretical and actual productivity of heavy equipment, calculate idle time, and optimize the number and combination of equipment to improve operational efficiency. The research was conducted over a seven-day period using the time study method at the South Cross Road Project Lot 2 in Blitar Regency. Data were obtained through observations of equipment cycle time, working duration, and the volume of completed excavation. The results revealed significant differences between theoretical and actual productivity. The rock drill breaker had a theoretical productivity of 489.28 m³/day and an actual productivity of 434.48 m³/day; the excavator showed 950 m³/day theoretically and 830.80 m³/day in the field; while the dump truck recorded 464.80 m³/day in theory and 388 m³/day in practice. Idle time was also found to be relatively high, with 1.99 hours/day for the rock drill breaker, 1.71 hours/day for the excavator, and 3.51 hours/day for the dump truck. After optimization through adjustments in equipment quantity and standardizing the work duration to six days, idle time was successfully reduced to 0.98 hours/day, 0.66 hours/day, and 0.14 hours/day, respectively. These findings highlight that proper planning of heavy equipment, in terms of both quantity and working time, plays a critical role in enhancing work efficiency in drainage excavationprojects.